New types of stable whistler nonlinear waveguides - Davydova, T.A.; Zaliznyak, Yu.A. (Вопросы атомной науки и техники, 2000)
The investigation of stationary whistler wave propagation in the framework of generalized nonlinear Shrödinger equation (GNSE) including fourth-order dispersive effects and saturable nonlinearity is performed. A novel class of whistler waveguides with a curved wave front is predicted. Necessary condition for different nonlinear structures formation, their spatial profile and stability properties are studied both analytically and numerically.